Dimensional instabilities of polyester and polyolefin films as origin of delamination in laminated multilayer. Issue 4 (22nd November 2016) - Dubelley, Florence; Planes, Emilie; Bas, Corine; Pons, Emmanuelle; Yrieix, Bernard; Flandin, Lionel
ABSTRACT: Polymer–metal multilayer films provide attractive barrier properties to air and water, provided by several films bonded together. Used in high temperature and humidity, the delamination is the most common degradation mechanism. This mode of failure is critical because it leads to premature loss of barrier properties. Therefore, delaminations limit the use of multilayer in these conditions. Delamination should result from interfacial shear stress, and plausibly from difference of shrinkage of the films, due to relaxation of internal stress. A method was developed for measuring the deformations of each individual film. The measurements indicate that the shrinkage is anisotropic and controls the decohesion in the multilayer. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 309–319 Abstract : In stacked films, interfacial delamination is a common and well‐identified problem. This failure mechanism reduces the use of multilayer polymer systems. Unfortunately this degradation might originate from a series of very dissimilar causes. This work details why the difference in dilatation and/or shrinkage between assembled films should be considered as a very plausible cause for interfacial separations.